INOVASI PENDIDIKAN AKHLAK BERBASIS MANAJEMEN QOLBU - Nurotun Mumtahanah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2011)
Abstract: Innovation of educationisan effort to make changesin ordertoget thingsbetterin thefield ofimprovement of education system. Moral education based on Qalbu management is a character education mixed with Qalbu management such as always learning to clean heart, sincerein carrying outtasks andduties, practice moral teachings that have been acquired in everyday life, andthe ways to make moral educational innovations based on Qalbu management such as worshipping the true, noble, constant learning, working hard withintelligentandsincere, humblein life, help others, purify your hearts, and always learntointrospectthemselves. Truly, character dependson Qalbu. Good Qalbu make good morals, bad Qalbu make bad character. So, Qalbuis the keyof person moral andthe morals that determine a person's ability to solveany problems thatcome up. Hanif Qalbu (straight, good) can not becreatedwithoutfaith, scienceandpractice. One way is to Qalbu Management.